1998
DOI: 10.1038/sj.bmt.1701073
|View full text |Cite
|
Sign up to set email alerts
|

Donor-derived Plasmodium vivax infection following volunteer unrelated bone marrow transplantation

Abstract: Summary:achieving haematological but not cytogenetic remission. She had no HLA-identical siblings. In March 1996, she developed bone pain, increasing hepatosplenomegaly, and A 14-year-old girl from the UK underwent volunteer unrelated donor bone marrow transplant (VUD BMT) a rising white cell count. Her peripheral blood film showed 10% blasts, although cytogenetic analysis remained for accelerated phase chronic myeloid leukaemia. On day +40 she became febrile, and peripheral blood unchanged. She was treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Viable asexual trophozoites of P. vivax in infected reticulocytes (or erythroblasts) have indeed been observed in the bone marrow (95,(166)(167)(168)(169)(170)(171) and spleen (172). In one case, a subpatent parasitemia confirmed by PCR contrasted with a ruptured spleen very heavily laden with P. vivax-infected reticulocytes (175).…”
Section: A Plausible and Testable Hypothesis On Pathogenesismentioning
confidence: 99%
“…Viable asexual trophozoites of P. vivax in infected reticulocytes (or erythroblasts) have indeed been observed in the bone marrow (95,(166)(167)(168)(169)(170)(171) and spleen (172). In one case, a subpatent parasitemia confirmed by PCR contrasted with a ruptured spleen very heavily laden with P. vivax-infected reticulocytes (175).…”
Section: A Plausible and Testable Hypothesis On Pathogenesismentioning
confidence: 99%
“…22 Transfusion-transmitted malaria has been reported previously and represents a potential problem in blood transfusions and HCT. 23,24 Malaria as a complication in HCT is extremely unusual. One case of Plasmodium falciparum transmission after sibling allogeneic HCT and two of Plasmodium vivax, one after unrelated HCT and one recrudescence after autologous HCT, have been reported.…”
Section: Parasitesmentioning
confidence: 99%
“…One case of Plasmodium falciparum transmission after sibling allogeneic HCT and two of Plasmodium vivax, one after unrelated HCT and one recrudescence after autologous HCT, have been reported. [24][25][26] The risk is likely to be dependent on the geographical location of both patient and donor. In malaria nonendemic areas such as the United States, the estimated incidence of malaria transmission by blood transfusion is one per one million units.…”
Section: Parasitesmentioning
confidence: 99%
“…4 In addition, two case studies reported P. vivax infections after autologous bone marrow transplantation and a third one documented an accidental P. vivax infection due to bone marrow transplantation between a malaria infected donor and a malaria free recipient. [5][6][7] In Brazil, one patient with persistent thrombocytopenia and an enlarged spleen was diagnosed with chronic P. vivax malaria after the finding of schizonts in the bone marrow aspirate. 8 The hematological changes seen in patients with malaria include anemia, neutropenia, reactive lymphocytosis, monocytosis, eosinopenia , neutrophil leukocytosis and thrombocytopenia.…”
Section: Introductionmentioning
confidence: 99%